2012
DOI: 10.1208/s12249-012-9899-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effect of Seeds and Callus of Nigella sativa L. Extracts on Mix Glial Cells with Regard to Their Thymoquinone Content

Abstract: Anti-inflammatory effect of the alcoholic extracts of N. sativa seeds and its callus on mix glial cells of rat with regard to their thymoquinone (TQ) content was investigated. Callus induction was achieved for explants of young leaf, stem, petiole, and root of N. sativa on solid Murashige and Skoog (MS) medium containing 2,4-D (1 mg/l) and kinetin (2.15 mg/l). TQ content of the alcoholic extracts was measured by HPLC. Total phenols were determined using Folin-Ciocalteu method and antioxidant power was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 34 publications
0
47
0
1
Order By: Relevance
“…Results confirmed that TQ content of the callus of leaf was 12 times higher than that measured in the seeds extract. Studies on the inflamed rat mix glial cells revealed significant reduction in the nitric oxide production in the presence of 0.2 to 1.6 mg/mL of callus extract and 1.25 to 20 µL/mL of the seed extracts [68] . Osteoporosis has been linked to oxidative stress and inflammation.…”
Section: Anti-inflammatory and Analgesic Activitymentioning
confidence: 95%
“…Results confirmed that TQ content of the callus of leaf was 12 times higher than that measured in the seeds extract. Studies on the inflamed rat mix glial cells revealed significant reduction in the nitric oxide production in the presence of 0.2 to 1.6 mg/mL of callus extract and 1.25 to 20 µL/mL of the seed extracts [68] . Osteoporosis has been linked to oxidative stress and inflammation.…”
Section: Anti-inflammatory and Analgesic Activitymentioning
confidence: 95%
“…TQ treatment had no significant effects on total plasma IgE or ovalbumin-specific IgE levels, and the intra-gastric treatment of mice with TQ did not affect IL-4, IL-5, IL-10 or IFNγ secretion by mesenteric lymphocytes after ex vivo re-stimulation with ovalbumin [34]. Recently, TQ was demonstrated to significantly reduce NO production in LPS-challenged primary glial cells isolated from Wistar rats [49].…”
Section: Effects Of Tq On Inflammationmentioning
confidence: 97%
“…These pharmacological effects include hypoglycemic [28][29][30][31], antihypertensive [32], antiinflammatory [33,34], and antioxidant [35,36] actions. Besides, there has been a surge of interest in studying the beneficial effects of NS in the treatment of cardiovascular diseases [20], cancer [37], [38] and gastrointestinal disorders [39].…”
Section: Biological Activitiesmentioning
confidence: 99%